Characteristics associated with healthcare independence among autistic adults. (July 2022) - Longo, Anne; Gilmore, Dan; Garvin, Jennifer; Hyer, J. Madison; Coury, Daniel; Hanks, Christopher; Moffatt-Bruce, Susan; Hess, Amy; Hand, Brittany N.
Abstract: Background: Healthcare independence refers to someone's ability to assume responsibility for their own health and complete tasks like taking medication as prescribed or scheduling healthcare appointments. Prior studies have shown that autistic people tend to need more support with healthcare tasks than people with other chronic conditions. We sought to identify modifiable and non-modifiable factors linked with healthcare independence among autistic adults. Method: We conducted a cross-sectional survey to examine how executive functioning skills, restrictive and repetitive behaviors, gender, education, and age were linked with healthcare independence among this population. Participants included: (a) autistic adults (n = 19) who are their own legal guardian, who participated via self-report; and (b) family members of autistic adults with a legal guardian (n = 11), who provided proxy-reports. Results: Findings differed between self- and proxy-reports. Among autistic adults who self-reported, difficulties in executive functioning were strongly linked with less healthcare independence. Among proxy-reports, greater restrictive and repetitive behaviors were strongly linked with less healthcare independence. According to the proxy-reports, having not completed high school, being older during the healthcare transition, and being male were all independently linked with less healthcare independence. Conclusions: Interventions aimed at supporting executive functioning, providing opportunities to increase independence with healthcare tasks, and reducing the extent to which restrictive and repetitive behaviors interfere with daily activities may be viable options for supporting healthcare independence among autistic adults. Our findings are an important first step for future initiatives to better identify individuals who need additional care coordination, supports, or services to maximize healthcare independence. Highlights: We examined factors linked with healthcare independence among autistic adults. Factors linked with healthcare independence differed between self- and proxy-report. Self-management skills may be a viable target to improve healthcare independence. Having a legal guardian, being male, not having completed high school, and being older at time of healthcare transition were independent factors that may indicate a higher need for support.